Evaluation of Heavy Metals Level and their Potential Effects to Water, Sediment, and Water Hyacinth Plants in Opa Reservoir, Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria - K. T. Ogundele; O. W. Makinde; E. A. Oluyemi; A. S. Kayode; S. O. Afolabi; O. A. Omisore (Journal of Applied Sciences and Environmental Management, 2024)
The contamination of the aquatic ecosystem with heavy metals has become a rising global concern due to their possible adverse health effects on human beings and the environment. Hence, the objective of this paper was to evaluate the levels of  Fe, Cu, Cd, Zn, Pb, As, and Cr and their potential effects on water, sediment, and water hyacinth plants in Opa Reservoir, Obafemi Awolowo University, Ile-Ife, Osun State, Nigeria using Atomic Absorption Spectrometry. The concentration of heavy metals in the hyacinth samples varied from 0.002 ± 0.000ppm to 0.5 ± 0.000ppm exceeding permissible limit except for Cu, Zn, and Fe. The metals in water samples ranged between 0.003 ± 0.001ppm to 0.5 ± 0.000ppm also surpassing the concentration limit established by WHO with only Cu, Zn, and Fe having lower concentrations. Sediment samples revealed a high concentration, varying from 0.005 ± 0.000ppm to 4.150 ± 0.002ppm. The values obtained were far above the permissible values set by WHO with only Zn, Fe, and As having lower concentrations. The contamination factor analysis indicated generally low contamination factor with the exception of Fe and Cr which showed moderate contamination. Although the pollution load index and geo accumulation index revealed that all metals were within the range of unpolluted geo-accumulation index, enrichment factor indicated varying degrees of contamination. While some metals exhibited depletion to minimal enrichment, others revealed significant or even extremely high enrichment pollution index. Considering the pollution status of the Opa reservoir, it is therefore recommended that regular monitoring of the reservoir be put in place to ensure the safety of human and aquatic ecosystems in general.